The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1002/eat.23412
|View full text |Cite
|
Sign up to set email alerts
|

Enduring value of perfectionism and maturity fears for predicting eating disorder maintenance over 10‐, 20‐, and 30‐year follow‐up

Abstract: Objective The Eating Disorder Inventory provides a theoretically informed multidimensional assessment of eating disorder symptoms and associated psychological factors widely used to examine the development and maintenance of eating disorders. Yet, mixed findings for some factors raise questions about whether their prognostic value varies as a function of duration of follow‐up or type of eating pathology studied. Method The current study compared prognostic value of perfectionism, maturity fears, and interperso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Motivation to recover is frequently low, due to perceived benefits of restrictive eating behaviors ( 28 ). The illness has been associated with high maturity fear, intolerance of uncertainty, perfectionism, anxiety, trauma, cognitive rigidity and alexithymia ( 13 , 26 , 29 36 )—however, these associations are typically measured quantitatively and thus limited to binary, researcher-derived constructs (impacting interpretive potential). Deriving a more nuanced understanding of these cognitions from the words of those who experience them may be vital to the development of novel therapeutic techniques that enhance interoception, motivation for change and self-efficacy and to understanding why existing treatments aren’t successful for many individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Motivation to recover is frequently low, due to perceived benefits of restrictive eating behaviors ( 28 ). The illness has been associated with high maturity fear, intolerance of uncertainty, perfectionism, anxiety, trauma, cognitive rigidity and alexithymia ( 13 , 26 , 29 36 )—however, these associations are typically measured quantitatively and thus limited to binary, researcher-derived constructs (impacting interpretive potential). Deriving a more nuanced understanding of these cognitions from the words of those who experience them may be vital to the development of novel therapeutic techniques that enhance interoception, motivation for change and self-efficacy and to understanding why existing treatments aren’t successful for many individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Some empirical research has found that perfectionistic traits are significant predictors of ED symptom severity and a maintaining factor for partial or full-blown EDs over time, even at 10-year [85], 12-year [86], and 30-year follow-ups [87]. Perfectionism has also been shown to predict worse therapeutic outcomes at a 16-year follow-up [88].…”
Section: Cognitive Patternsmentioning
confidence: 99%
“…Perfectionism has also been shown to predict worse therapeutic outcomes at a 16-year follow-up [88]. Furthermore, some longitudinal studies have shown that greater maturity fears at baseline predict a higher drive for thinness and more bulimic symptoms at 10-year, 20-year, and 30-year follow-ups [87], as well as worse AN outcomes at a 20-year follow-up [89]. Finally, body checking (i.e., scrutinizing one's body in a mirror, checking the fit of clothes, measuring body parts) has emerged as both a maintaining factor of eating pathologies and a trans-diagnostic treatment target [90].…”
Section: Cognitive Patternsmentioning
confidence: 99%